Environmental determinants of different blood lead levels in children: A quantile analysis from a nationwide survey. (January 2015) - Etchevers, Anne; Le Tertre, Alain; Lucas, Jean-Paul; Bretin, Philippe; Oulhote, Youssef; Le Bot, Barbara; Glorennec, Philippe
Abstract: Blood lead levels (BLLs) have substantially decreased in recent decades in children in France. However, further reducing exposure is a public health goal because there is no clear toxicological threshold. The identification of the environmental determinants of BLLs as well as risk factors associated with high BLLs is important to update prevention strategies. We aimed to estimate the contribution of environmental sources of lead to different BLLs in children in France. We enrolled 484 children aged from 6 months to 6 years, in a nationwide cross-sectional survey in 2008–2009. We measured lead concentrations in blood and environmental samples (water, soils, household settled dusts, paints, cosmetics and traditional cookware). We performed two models: a multivariate generalized additive model on the geometric mean (GM), and a quantile regression model on the 10th, 25th, 50th, 75th and 90th quantile of BLLs. The GM of BLLs was 13.8 μg/L (= 1.38 μg/dL) (95% confidence intervals (CI): 12.7–14.9) and the 90th quantile was 25.7 μg/L (CI: 24.2–29.5). Household and common area dust, tap water, interior paint, ceramic cookware, traditional cosmetics, playground soil and dust, and environmental tobacco smoke were associated with the GM of BLLs. Household dust and tap water made the largest contributions to both the GM and the 90th quantile of BLLs. The concentration of lead in dust was positively correlated with all quantiles of BLLs even at low concentrations. Lead concentrations in tap water above 5 μg/L were also positively correlated with the GM, 75th and 90th quantiles of BLLs in children drinking tap water. Preventative actions must target household settled dust and tap water to reduce the BLLs of children in France. The use of traditional cosmetics should be avoided whereas ceramic cookware should be limited to decorative purposes. Highlights: We estimated the contribution of environmental sources of lead to different BLLs. Household dust and tap water were the major contributors. Ceramic cookware and traditional cosmetics were also strong contributors. Lead in dust was positively correlated with all quantiles of BLLs without threshold. Lead concentrations in tap water above 5 μg/L were associated with GM, 75th and 90th quantiles of BLLs.